Generation of a H9 Clonal Cell Line With Inducible Expression of NUP98-KDM5A Fusion Gene in the AAVS1 Safe Harbor Locus - Domingo-Reinés, Joan; Martínez-Navajas, Gonzalo; Montes, Rosa; Lamolda, Mar; Simón, Iris; Castaño, Julio; Ríos-Pelegrina, Rosa; Lopez-Hidalgo, Javier Luis; García del Moral, Raimundo; Marchal, Juan A.; Real, Pedro J.; Ramos-Mejía, Verónica (Frontiers in Cell and Developmental Biology, 2022)
Pediatric acute myeloid leukemia (AML) is a rare and heterogeneous disease that remains the major cause of mortality in children with leukemia. To improve the outcome of pediatric AML we need to gain knowledge on the biological bases of this disease. NUP98-KDM5A (NK5A) fusion protein is present in a particular subgroup of young pediatric patients with poor outcome. We report the generation and characterization of human Embryonic Stem Cell (hESC) clonal lines with inducible expression of NK5A. Temporal control of NK5A expression during hematopoietic differentiation from hESC will be critical for elucidating its participation during the leukemogenic process.